Philosophical preconditions of political theories. - Shevchuk, Dmytro (Actual Problems of Mind, 2017)
The author postulates a necessity of a reconsideration of the foundations of a political theory by appealing to the classical tradition and its critical rethinking. The paper proposes three approaches to an understanding of the political, which underlies the political world (as antagonistic, agonistic, imaginary and symbolic)- The main task of a political theory should be the prevention of the transformation of human being into a political object.